Bjerkandera adusta TM11 for the bioremediation of fluoroquinolone antibiotics spiked in wastewater: A sustainable approach to pharmaceutical contaminant biotransformation - Hasna Befenzi; Amine Ezzariai; Jihane Baghor; Hamza Arrach; Jean Armengaud; Mélodie Kielbasa; Annick Doan; Julien Lambert; Anne Lomascolo; Quentin Albert; Craig B. Faulds; Giuliano Sciara; et al. (Ecotoxicology and Environmental Safety)
Global antibiotic consumption is increasing dramatically. Antibiotic release into the environment, primarily through wastewater discharge, has serious impacts for human and animal health and microbial ecosystems. To address this issue, white-rot fungi present a promising solution, as they possess oxidative enzymes that can degrade these pollutants. Here we investigated the effectiveness of the white-rot fungus Bjerkandera adusta TM11 for removing three persistent fluoroquinolone antibiotics, i.e. levofloxacin, ciprofloxacin, and enrofloxacin, in real wastewater. The three antibiotics were added to the wastewater separately at a concentration of 30 mg/L and together in a cocktail at 10 mg/L, then incubated for 9 days. LC-MS/MS analysis and anti-microbial assay (against Escherichia coli) demonstrated complete removal of levofloxacin by day 7. However, ciprofloxacin and enrofloxacin biotransformed into degradation products that still had antimicrobial activity, with degradation efficiencies reaching 82 % and 99 %, respectively, by day 7. Proteomic analysis identified 21 fungal heme peroxidases. Versatile peroxidase was the most strongly-produced enzyme potentially involved in antibiotic biotransformation. Degradation products were characterized by LC-MS/MS analysis, and a degradation pathway was proposed based on these findings.